Number of seminal follicles and ovarioles in Fulgoromorpha (Hemiptera: Auchenorrhyncha): Variability and evolutionary trends - Valentina G. KUZNETSOVA; Natalia V. GOLUB; Anna MARYAŃSKA-NADACHOWSKA (European Journal of Entomology)
In this paper data on the number of follicles in testes and the number of ovarioles in ovaries of planthoppers (Hemiptera: Fulgoromorpha) are summarised and discussed. Fulgoromorpha include about 14,000 described species belonging to 21 families distributed throughout the world. The number of follicles is known for 186 species, 123 genera and 17 families, and the number of ovarioles is known for 52 species, 44 genera and 11 families. Almost 80% of the species studied belong to the families Dictyopharidae, Delphacidae, Issidae, Cixiidae and Achilidae. The number of follicles per testis and ovarioles per ovary varies within similar ranges, from 2 to 30 and from 3 to just over 30, respectively. The predominant number of follicles is 6, which is found in more than one third of the species and in almost all of the families studied. This number is considered as an ancestral trait for Fulgoromorpha. In each family, the ancestral number can vary both upwards or downwards, probably due to either polymerization or oligomerization. In the more basal families, a decreasing trend clearly predominates, whereas an increasing trend predominates in the more advanced families. As for the numbers of ovarioles, they tend to vary within families, with rare exceptions (e.g., Dictyopharidae), but that is probably due to the lack of data.